Effect of Pregnancy Exercise on Lower Back Pain in Pregnant Women in The Village of The Working Area of Medan Tuntangan Public Health Center - Tampubolon, Emelia; Fransysca, Helena (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Back pain is pain that is in the lumbar, lumbar sacral, or in the neck area. Back pain occurs due to muscle strain and pressure on nerve roots. The research method uses a quasi-experimental design with One group pretest-post test design. The population in this study were pregnant women in the third trimester in the working area of ​​the Medan Tuntungan Health Center as many as 30 people and all of them were used as samples (total sampling). The results of the study were 21 respondents (70%) moderate pain, 6 respondents (20%) had mild pain, 3 respondents (10%) had severe but controlled pain and no respondent had no pain and experienced severe uncontrolled low back pain. After the demonstration there were 20 respondents (66.7%) mild pain, 7 respondents (23.3%) no pain, 3 respondents (10%) moderate low back pain, and none of the respondents experienced controlled and uncontrolled severe low back pain. . Paired sample t-test analysis obtained a p-value of 0.000 (p-value <0.05). This means that there is an effect of pregnancy exercise on low back pain in pregnant women. It is expected that health workers will provide counseling to pregnant women about the benefits of pregnancy exercise to prevent back pain complaints.